Assessment methodology and performance indicators for HVDC grid protection strategies. Issue 15 (23rd August 2018) - de Freitas, Guilherme Dantas; Ismail, Boussaad; Bertinato, Alberto; Raison, Bertrand; Niel, Eric; Poullain, Serge; Luscan, Bruno
Abstract : This study presents an assessment methodology of protection strategies for meshed grids. It also proposes the computation of two performance indicators to evaluate protection strategies through a reliability and speed perspective. The Monte Carlo method is used to calculate the two indicators proposed. These two indexes can be used as criteria for comparison between protection strategies. Owing to the increasing debate around the protection for high‐voltage DC (HVDC) grids, three proposals of protection of HVDC grids were chosen as application cases.